Child Care Pattern Model: A Nursing Science and Islamic Education Perspective - Ilahiyani, Vinasti; Septianisa, Riska Elora; Putri, Muthia Amelia; Al Zahara, Al Zahara; Azmi, Kayla Sabitul; Supriyadi, Tedi (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
Parenting plays an important role in shaping the character and health of children physically, mentally, and spiritually. This study aims to formulate a holistic parenting model by integrating nursing science and Islamic education approaches to address modern parenting challenges. This study used a qualitative method with a case study design, involving four participants, consisting of pediatric nurses and Islamic religious educators. Interviews showed that both nursing science and Islam emphasize the importance of meeting children's needs holistically through love (asih), physical care (asuh), and intellectual-social stimulation (asah). Meanwhile, Islam adds spiritual values and role modeling through prophetic parenting. The democratic parenting model is the most appropriate because it encourages two-way communication, empathy, and value-based discipline. Nurses play an important role in assisting parents through contextualized and collaborative education. The findings conclude that the integration of nursing and Islamic values in parenting can create a generation that is physically healthy, mentally strong, and noble. This research is expected to be a practical reference in local value-based parenting that is relevant to the context of Indonesian society.   Keywords: parenting model, pediatric nursing, holistic parenting, Islamic education, Prophetic parenting